Photophysical Properties of Oligo(phenylene ethynylene) Iridium(III) Complexes Functionalized with Metal‐Anchoring Groups. Issue 12 (21st March 2016) - Ponce, Julia; Aragó, Juan; Vayá, Ignacio; Magenti, Jorge Gómez; Tatay, Sergio; Ortí, Enrique; Coronado, Eugenio
Abstract: The electrochemical and photophysical properties of a family of conjugated ligands and their iridium(III) cyclometallated complexes are described. They consist of a series of monocationic Ir III bis‐2‐phenylpyridine complexes with p ‐phenylethynyl‐1, 10‐phenanthroline ligands of different length. The structure of these ligands includes terminal acetylthiol or pyridine groups, which can provide good electrical contacts between metal electrodes. Cyclic voltammetry, absorption and emission spectroscopy, laser flash photolysis and density functional theory calculations reveal that the high conjugation of the diimine ligand affords small energy gaps between the frontier orbitals. Nevertheless, the nature of the terminal substituents and the extent of the conjugation in the diimine ligand have little influence on the photophysical features at room temperature. The spectroscopic data and theoretical calculations agree that the charge‐transfer nature of the emitting excited state is maintained along the series at room temperature, whereas in rigid matrices ligand‐centred states also contribute to the low‐temperature emission. The good conducting features of the diimine ligands, the small dependence of the HOMO–LUMO (HOMO = highest occupied molecular orbital, LUMO = lowest unoccupied molecular orbital) gaps of these complexes on the ligands and the charge‐transfer nature of the emitting excited state make these complexes promising test beds for the study of photoconducting phenomena in molecular junctions. Abstract : The charge‐transfer nature of the emitting excited state, the small dependence of the HOMO–LUMO gap on the molecular length, the presence of metal‐anchoring groups, and the good conducting features of the diimine ligands make our iridium(III) complexes promising test beds for the study of photoconducting phenomena in molecular junctions.